The impact of different control type on video sharing via educational platforms in developing robot programming skills for third- intermediate students in the Kingdom of Saudi Arabia - Alfaifi, Sultan Ibrahim (Journal of Educational and Psychological Sciences, 2020)
The current research aimed to identify the impact of different control patterns on participatory videos across educational platforms in developing robot programming skills Contained in the book of computer (unit- 4) (Robot Siddiqui – Smart devices and Robot) for third- grade intermediate students in Kingdom of Saudi Arabia. The researcher used the quasi-experimental method, the study sample consisted of (50) students from the intermediate. They were randomly assigned to a first experimental group of (25) students who presented the participative video clips with the learner control pattern, (25) Students were given participatory video clips in the program control mode, The researcher designed the educational control patterns of the participatory videos based on the Aljazar model (2002) and the Khamis model (2003) of the design of education After the experience and study tools are applied, they are a test of my score and the programming skills card, The results revealed that there were statistically significant differences at the level (0.05) between the average scores of the two study groups in the test and the observation card, and the differences were in favor of the first experimental group with which the learner control pattern was used with video clips. The study recommended that the services of collaborative video platforms should be utilized in the learning process, and that participatory videos be produced using a learner control pattern in other courses and used in different learning situations.
Keywords: Control type; Participatory video; Robot programming skills